2020
DOI: 10.1186/s42155-020-00120-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous treatment of vascular access-site complications: a ten years’ experience in two centres

Abstract: Background The spread of percutaneous arterial catheterization in diagnostic and therapeutic procedures has led to a parallel increase of vascular access site complications. The incidence of these events is between 0.2–1%. A detailed analysis of injuries by type of procedure shows a higher incidence of injuries after therapeutic procedures (3%) than those observed for diagnostic ones (1%), due to the greater size of the vascular devices used and the necessity to frequently administer anticoagulant and antiplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
6
15
0
Order By: Relevance
“…Ipsilateral imaging (ie the RAO for the right CFA) is considered to be the best orientation to display the bifurcation of the deep and superficial femoral branches, 19 but this view was used exclusively in only 26% of included cases. CFA imaging performed in the AP view (≤15°) was associated with significantly lower radiation dose to the patient, but imaging in the AP view only may lead to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ipsilateral imaging (ie the RAO for the right CFA) is considered to be the best orientation to display the bifurcation of the deep and superficial femoral branches, 19 but this view was used exclusively in only 26% of included cases. CFA imaging performed in the AP view (≤15°) was associated with significantly lower radiation dose to the patient, but imaging in the AP view only may lead to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support those of Zurcher et al, who reported a patient dose reduction of 40% when DSA was substituted by fluoroscopic imaging during endovascular aneurysm repairs, 18 and Pearl et al who concluded that DSA of the femoral artery should be replaced with fluoro save during cerebral angiography. 15 Ipsilateral imaging (ie the RAO for the right CFA) is considered to be the best orientation to display the bifurcation of the deep and superficial femoral branches, 19 but this view was used exclusively in only 26% of included cases. CFA imaging performed in the AP view (≤15°) was associated with significantly lower radiation dose to the patient, but imaging in the AP view only may lead to misdiagnosis.…”
Section: Femoral Imaging During Coronary Angiography -Implications For Patientsmentioning
confidence: 99%
“…Patients with asymptomatic PSA underwent treatment only if the PSA did not resolve and showed an increase in size within a week or if the patient became symptomatic [7]. Patients with symptomatic PSA were treated with replacement of the pressure bandage, UGC, UGTI, or open surgical repair [1,[4][5][6][7]. In patients whose coagulation status was normal, in whom PSA was detected within a week after the procedure, the PSA sac was superficial, simplex, and small (<20 mm), and the PSA neck was long and narrow, replacement of the pressure bandage or UGC was attempted [7,16].…”
Section: Pseudoaneurysm Treatmentmentioning
confidence: 99%
“…Pseudoaneurysm (PSA) development is the second most common complication in those undergoing procedures that require an arterial puncture [4]. Its prevalence has been reported to range from 0.05% to 6%, with a higher incidence after therapeutic interventions than after diagnostic catheterizations [1,[4][5][6][7]. The etiology of PSA is multifactorial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation